2016
DOI: 10.1002/slct.201500018
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) pseudohalide complexes with isomeric N2O donor Schiff base ligands: Synthesis, characterization and molecular dynamics simulations of interactions with DNA

Abstract: Two new square planar copper(II) complexes, [Cu(L 1 )(NCO)] (1) and [Cu(L 2 )(N 3 )] (2), where HL 1 = 1-(-1-(2-(diethylamino)ethylimino)ethyl)naphthalen-2-ol and HL 2 = 2-(-(2-(diethylamino) ethylimino)methyl)naphthalen-1-ol, have been synthesized and characterized by elemental analysis, IR, UV-VIS and single-crystal X-ray diffraction studies. Interaction of the complexes with calf thymus DNA (c t DNA) was studied by UV-VIS spectroscopy that revealed complex 2 had a slightly greater affinity for DNA. The mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The bands in the range of 2792–2995 cm −1 due to alkyl C–H bond stretching vibrations are customarily noticed in the IR spectra of both complexes . A strong band at 2220 cm −1 (in 1 ) indicates the presence of terminal azide …”
Section: Resultsmentioning
confidence: 89%
“…The bands in the range of 2792–2995 cm −1 due to alkyl C–H bond stretching vibrations are customarily noticed in the IR spectra of both complexes . A strong band at 2220 cm −1 (in 1 ) indicates the presence of terminal azide …”
Section: Resultsmentioning
confidence: 89%
“…As complex 1 is chiral (complex 1 crystallizes in chiral space group) and complex 2 is achiral, it may be concluded that the chirality of complex 1 played very significant role to binding of chiral DNA molecule. It could also be found in literature that when two complexes were otherwise similar structurally, a chiral complex had a greater affinity for DNA …”
Section: Description Of Structuresmentioning
confidence: 86%